Classification of Capacitor Bank Switching Using Fuzzy Interference Systems in 230 kV Substation - Theerasak Patcharoen; Chaichan Pothisarn; Atthapol Ngaopitakkul; Santipont Ananwattanaporn; Praikanok Lertwanitrot; Suntiti Yoomak (My University, 2024)
Flexible AC transmission systems are used for enhancing the stability, transmission efficiency, and reliability of AC grids. Additionally, the most cost-effective devices for compensating reactive power are Mechanically Switched Capacitors (MSCs). This study proposes a novel algorithm for detection and capacitor bank switching transient signals in MSC, to prevent the protective relay maloperation by these transients. The Discrete wavelet transform (DWT) is used for effective time-frequency analysis and detection of measured three-phase current signals. DWT extracts the detailed wavelet coefficients of current signals at levels 1 to 30. In addition, the fuzzy inference system (FIS) has been used to determine the type of switching transient. The proposed combination of FIS and DWT has been tested on 230 kV substation and the result demonstrated precision for the identification and classification of both transient signals in MSC with 88% accuracy rate.
Keywords: Power Systems Fault Detection; Power Systems and Technologies; Elevator Systems and Control